Parametric influence on convective heat transfer for an outlet guide vane. (17th August 2016) - Luo, Lei; Wang, Chenglong; Wang, Lei; Sundén, Bengt; Wang, Songtao
ABSTRACT: Improved understanding of the impact of the operating conditions on the heat transfer and fluid flow behaviors of an outlet guide vane (OGV) is essential for accurate prediction of the lifetime of jet engines. In this article, the heat transfer characteristics of an OGV at various Reynolds numbers (Re), free stream turbulence levels, Mach number (Ma), and surface roughness are studied numerically. The Re is kept at 300, 000 and 450, 000, respectively, the free stream turbulence intensity ranges from 3.2% to 13%, and the turbulent length scale is varied from 1.2 to 11 mm. The Ma is selected as 0.06, 0.25, and 0.35, and the sandy grain roughness height is increased from the smooth wall level up to 160 µm. Mid-span pressure coefficient and Nu distributions are presented. Basically, the heat transfer patterns and pressure profiles are weak functions of the Re and Ma. Increasing the Re slightly moves the transition position upstream, while the Ma has no effect on the transition process. On the suction side, the transition is induced by flow separation and a bump is visible in the pressure profile. However, the turbulence intensity, turbulence length scale, and surface roughness levels have significant effects on the heat transfer and pressure distributions. On the suction side, the bump is invisible and the "separation-induced transition" is replaced by the "by pass transition". It is also found that the transition position moves upstream as the turbulence intensity, length scale, and roughness level increase.